A Phase Ib/II Study of Gemcitabine and Docetaxel in Combination With Pazopanib for the Neoadjuvant Treatment of Soft Tissue Sarcomas. (8th October 2015) - Munhoz, Rodrigo R.; D'Angelo, Sandra P.; Gounder, Mrinal M.; Keohan, Mary L.; Chi, Ping; Carvajal, Richard D.; Singer, Samuel; Crago, Aimee M.; Landa, Jonathan; Healey, John H.; Qin, Li-Xuan; Hameed, Meera; et al.
Abstract: Author Summary : Lessons Learned : Our results highlight some of the challenges in the management of soft tissue sarcomas, which requires close cooperation between surgeons and medical oncologists and a careful selection of patients. The incidence of hepatotoxicity was a concerning finding and had been previously reported in patients treated with pazopanib. Although pharmacokinetic analysis was not part of this study, concomitant treatment with pazopanib has been recently reported to increase docetaxel exposure, which may explain the increased toxicity of combination regimens. It remains possible that lower doses of combined gemcitabine, docetaxel, and pazopanib may be tolerable. However, caution should be exercised in future trials investigating similar combinations. Background: For extremity soft tissue sarcomas (STS), surgical resection remains the standard of care, and the addition of chemotherapy is controversial. This was a phase Ib/II trial of neoadjuvant therapy for patients with STS. Methods: Patients with high grade, extremity STS of >8 cm and amenable to definitive resection were treated with up to four 21-day cycles of 900 mg/m 2 gemcitabine on days 1 and 8, 75 mg/m 2 docetaxel on day 8, and 400 mg of pazopanib daily (GDP), followed by surgery and, if indicated, radiation therapy. Primary and secondary endpoints (phase Ib portion) were the safety and rate of pathologic response. Results: The trial was discontinued because of slow accrual after inclusion of five patients (leiomyosarcoma: two; undifferentiated pleomorphic sarcoma: three). Two patients completed four treatment cycles: one underwent surgery and one had insufficient response and received additional therapies. Three patients discontinued treatment because of toxicity. Grade 3 adverse events included hypertension, fatigue, aspartate aminotransferase (AST) or alanine aminotransferase (ALT) elevation, hoarseness, and myelotoxicity. There were no complete or partial responses. One patient had ≥90% pathologic response. Among four patients who underwent resection, three remain free of disease, and one patient eventually relapsed. Conclusion: GDP combination used in the neoadjuvant setting resulted in significant toxicity; despite pathologic responses, no objective responses occurred.